Baseline assessment of staff perception of critical value practices in government hospitals in Kuwait - Talal ALFadhalah; Buthaina Al Mudaf; Haya Al Tawalah; Wadha A. Al Fouzan; Gheed Al Salem; Hanaa A. Alghanim; Samaa Zenhom Ibrahim; Hossam Elamir; Hamad Al Kharji (BMC, 2022)
Abstract Background Notification of laboratory-determined critical values is key for effective clinical decision making and is thus a consequential step in a patient's health care and safety. This study presents an overview of staff reporting policies and procedures concerning critical values in Kuwaiti governmental hospitals. Methods A cross-sectional descriptive study design was adopted. Study subjects were affiliated with laboratories from five government hospitals (four general and one sub-specialty hospital). All laboratory staff in every hospital were included. The Statistical Package for the Social Sciences (version 23) was used to analyse the collected data at a significance level of ≤ 0.05. Quantitative data analysis included univariate descriptive (means, medians, standard deviations, frequencies, percentages) and bivariate (chi-squared, ANOVA and Kruskal-Wallis tests) analyses. These analyses provided associations between participating hospitals and staff perceptions towards the policies and procedures surrounding critical values. Results 559 questionnaires were returned, a total response of 30.5% after those of 79 phlebotomists were excluded (eligible sample size n = 1833). The notification of critical values differs between participated laboratories in delivering protocol and time duration. Linked protocols between laboratories did not exist regarding policies and guidelines for applying the same procedures for critical value notification. There are differences in critical value limits among the participating laboratories. Conclusion This study is the first to survey laboratory staff perceptions of critical value practices in Kuwaiti government hospitals. Enhancing critical value reporting and policy is crucial for improving patient safety and to develop high-quality health services. The findings of this study can help policy makers implement future intervention studies to enhance laboratory practices in the area of critical values and improve patient safety and the quality of government hospital systems.